Islam, constitutional law, and human rights - Virgili, Tommaso, author.
1 online resource (xvi, 194 pages).
Keywords: "This book explores how Islam, its laws and principles, affects individual liberties. It focuses on the constitutions of Tunisia and Egypt, two countries which have experienced at least partial democracy following the Arab Spring. The work examines a number of sensitive topics from an Islamic perspective, and concludes with two specific case studies in the concerned countries"--